Comparative analysis of acceleration gradients for chip structures with different refractive indices - Vasyliev, A.V.; Bolshov, O.O.; Svistunov, O.O.; Povrozin, A.I.; Zaitcev, V.P.; Leshchenko, V.P.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2021)
The results of numerical studies of accelerating gradients in accelerators based on dielectric chip structures with different refractive indices, excited by a titanium-sapphire laser pulse, are presented. A comparative analysis of the influence of the refractive index on the rate of acceleration of electron bunches is carried out. Promising materials for the manufacture of dielectric laser accelerators are proposed.